INOVASI BROWNIES MENGGUNAKAN TEPUNG BEKATUL - Astiana, Rachmat; Tri Putri, Azizah (Bogor Hospitality Journal, 2025)
IIn Indonesia, Brownies are a sweet snack that is almost always found in various events that take place in the community. While the availability of bran itself is very abundant but unfortunately it has not been utilized optimally, including its use as a flour substitute for wheat so that the author is interested in conducting research on the use of bran flour as a basic ingredient for Brownies for this reason this study aims to determine the influence of organoleptic tests on bran Brownies, find out the public acceptance of bran brownie innovations and find out the best formulation in bran brownie innovation. With an experimental qualitative research method using hedonistic test analysis techniques or organoleptic tests. Based on the results of the panelist test, data was obtained that 43% of panelists liked Brownies with 100% bran flour, so it can be concluded that the use of 100% bran flour in Brownies can be well accepted by the community.